Performance of gas turbine cycles for combined cycle power plant - Mohd Khusairy Khadzir
This final year project is about to evaluate and compare the performance of different gas turbine cycles for proposed combined cycle plant that would produce 300 MW of power and to develop a computer program for each cycle to evaluate and compare the performance of different gas turbines cycles.